Diagnostic and prognostic value of galactose-deficient IgA1 in patients with IgA nephropathy: an updated systematic review with meta-analysis - Zeng, Qin; Wang, Wen-Ru; Li, Yi-Han; Liang, Ying; Wang, Xin-Hui; Yan, Lei; Yu, Ren-Huan (Frontiers in Immunology, 2023)
Objectives: Galactose-deficient IgA1 (Gd-IgA1) is a critical effector molecule in the pathogenesis of IgA nephropathy (IgAN), a leading renal disease without noninvasive assessment options. This updated systematic review aimed to determine the diagnostic and prognostic value of Gd-IgA1 assessment in biological fluids in patients with IgAN. Methods: PRISMA guidelines were followed in this review. We searched PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, China Biology Medicine disc, VIP Information/China Science and Technology Journal Database, and WANFANG for studies published between database inception and January 31, 2023. Eligible studies that evaluated aberrant IgA1 glycosylation in IgAN patients relative to controls were identified, and random effects meta-analyses were used to compare Gd-IgA1 levels in different groups. The quality of the evidence was assessed using the Newcastle-Ottawa Scale. This study was registered on PROSPERO (CRD42022375246). Findings: Of the 2727 records identified, 50 were eligible and had available data. The mean Newcastle-Ottawa Scale score was 7.1 (range, 6–8). Data synthesis suggested that IgAN patients had higher levels of blood and/or urine Gd-IgA1 compared with healthy controls (standard mean difference [SMD]=1.43, 95% confidence interval [CI]=1.19－1.68, P<0.00001), IgA vasculitis patients (SMD=0.58, 95% CI=0.22－0.94, P=0.002), and other kidney disease patients (SMD=1.06, 95% CI=0.79－1.33, P<0.00001). Moreover, patients with IgAN had similar levels of serum Gd-IgA1 compared to first-degree relatives (SMD=0.38, 95% CI= -0.04－0.81, P=0.08) and IgA vasculitis with nephritis patients (SMD=0.12, 95% CI= -0.04－0.29, P=0.14). In addition, ten studies demonstrated significant differences in serum Gd-IgA1 levels in patients with mild and severe IgAN (SMD= -0.37, 95% CI= -0.64－-0.09, P=0.009). Conclusions: High serum and urine Gd-IgA1 levels suggest a diagnosis of IgAN and a poor prognosis for patients with this immunological disorder. Future studies should use more reliable and reproducible methods to determine Gd-IgA1 levels.